2022
DOI: 10.1158/1538-7445.am2022-5177
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 5177: Lymph node ratio is superior to AJCC N stage for predicting recurrence in papillary thyroid carcinoma

Abstract: Objective: Recently, lymph node ratio (LNR) has emerged as an alternative to American Joint Committee on Cancer (AJCC) N stage, with superior prognostic value. The utility of LNR in Middle Eastern Papillary thyroid carcinoma (PTC) remains unknown. Therefore, we retrospectively analyzed a large cohort of 1407 PTC patients for clinico-pathological associations of LNR. Methods: Receiver operating characteristics (ROC) curve was used to determine the cut-off for LNR. We also performed multivariate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Ho et al (2021) further evaluated the prevalence of DM in well-differentiated thyroid carcinoma based on their lymph node (LN) burdens and found that the metastasis prevalence increased in a manner dependent on LN numbers 15 . Besides, the metastatic lymph node ratio has been found to be superior to N stage in predicting PTC recurrence 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ho et al (2021) further evaluated the prevalence of DM in well-differentiated thyroid carcinoma based on their lymph node (LN) burdens and found that the metastasis prevalence increased in a manner dependent on LN numbers 15 . Besides, the metastatic lymph node ratio has been found to be superior to N stage in predicting PTC recurrence 6 .…”
Section: Discussionmentioning
confidence: 99%
“…To enable early identification of patients with DM risks, several clinic-pathological features have been proposed. Older age 3 , male sex 4 , and pathologic factors like T stage 5 , lymph node metastasis (LNM) 6 , and extrathyroidal extension (ETE) 7 were reported to predict DM. Besides, genetic alterations among candidate genes were also postulated to improve the risk stratification of TC in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of nine retrospective studies showed that LNR was an independent predictor of loco-regional recurrence in metastatic PTC [11]. Furthermore, Parvathareddy et al reported that LNR was a better predictor of tumor recurrence than the American Joint Committee on Cancer (AJCC) N stage (odds ratio 1.96 vs. 1.30, p value 0.0184 vs. 0.3831) [12]. The aim of this study was to validate the relationship between LNR and the risk of recurrence in patients with PTC and only one to five LNs examined.…”
Section: Introductionmentioning
confidence: 99%